MATHEMATICAL MODELING OF THE DEVELOPMENT TECHNOLOGY OF SELECTED LEATHER FOR THE TRANSFORMATION ASSORTMENT - Turdiyeva, O`giloy; Khojiyev, Abdurakhim (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In this article, calf, cow, sheep, and goat skins were processed for experimental options for the assortment of transformation bags, their physical-mechanical and chemical composition was determined, and a mathematical model was developed based on them. Based on the physico-mechanical and chemical composition, a mathematical model was developed and the values ​​of the coefficients determined on the basis of the mathematical models were discussed The values ​​of the coefficients determined among the mathematical models of leather selected for the transformation assortment were discussed and the most useful one was selected. The chemical composition, physico-mechanical properties of calf, cow, sheep and goat skins obtained for experimental options were determined and a mathematical model was created and analyzed, its mathematical model was developed and useful leather for bags was determined.